Madam C.J. Walker : INVENTOR AND BUSINESSWOMAN - Simons, Lisa M. Bolt, 1969-; Butzer, Anna; Nuytten, Bobbie (North Mankato, Minnesota : Capstone Press, a Capstone imprint, 2018)
Madam C.J. Walker wasn't just an inventor. She was also a political activists and businesswoman. Learn more about how she not only fought for civil rights, but became one of the most successful African-American business owners ever.
Includes bibliographical references (page 23) and index.
Interest age level: Ages 6-9.
Keywords: Walker, C.J., Madam, -- 1867-1919 -- Juvenile literature; African American women executives -- Biography -- Juvenile literature; Women millionaires -- Biography -- Juvenile literature -- United States